BF3·Et2O Promoted Sulfuration of Steroidal Sapogenins. Issue 6 (2nd June 2015) - Wang, Jun; Wu, Jingjing; Tian, Weisheng
Abstract: A reaction between steroidal sapogenins and hydrogen sulfide promoted by BF3 ·Et2 O is described. The thiodiosgenin and thiotigogenin comprising a sulfur atom on the F ring can be easily afforded in one step under this mild reaction condition. Furthermore, a hypothetical mechanism is also shown. Abstract : The reaction between steroidal sapogenins and hydrogen sulfide catalyzed by BF3 ·Et2 O is described. The thiodiosgenin and thiotigogenin comprising a sulfur atom on the F ring have been synthesized under this mild reaction conditions.